DEVELOPING ENGLISH READING TEXT MATERIALS FOR CULINARY ART STUDENTS OF SMKN 1 KISARAN - Sri Wirdani Wulandari; Zainuddin (Universitas Negeri Medan, 2017)
This study is aimed to develop English reading materials for vocational school. This study was conducted by using Research and Development (R&D). The subject of this research was Grade X students of Culinary Art Department of SMKN 1 Kisaran, Asahan, Sumatera Utaraconsisting of 25 students. The data consist of syllabus, lesson plan, syllabus and existing materials. Instrument of collecting data were questionnaires and interview which were used to collect information about students’ needs and learning needs. The evaluation of existing reading materials showed that the existing reading materials are not intended for students of Culinary Art Department. The existing reading materials are intended for all vocational students. After the students’ need and reading materials had been analyzed, the new reading material was developed that considering the students’ need and the relevant with culinary. The genre of the reading texts which were developed is descriptive text.The product was validated by an English teacher and an English lecturer with the mean score is 4.1 from 5. The product is categorized as “Good and Relevant” reading materials.